PEMBUATAN DAN KARAKTERISASI BETON POLIMER DENGAN MENGGUNAKAN CAMPURAN BATU APUNG DAN AGREGAT PASIR SERTA TEPUNG KETAN DENGAN PEREKAT POLIESTER - ARIFAH HIDAYAH PULUNGAN (Saintia Fisika, 2013)
Research of polymer concrete had been made by using pumice, glutinous rice and sands. Research had been done in order to get the best combination of sands and pumice as independent variable with composition of variations to 30:60 g, 40:50 g, 50:40 g, 60:30 g, 70:20 g, 80:10 g, 90:0 g. Then, constant variable with composition 10 g glutinous rice, polyester 20 g as a glue in combination and thinner 10 g. Then, it was pressed by using Hot Comppressor for 30 minutes at temperature of 70 oC. The properties of polymer concrete has been analyzed that is physical properties such as water absorption, porosity, mechanical properties, impact test and bending strength test. The result of research showed that the best combination based on test was the combination of sands and pumice with ratio of 60:30 g and additional 10 g of as glutinous rice, as binding 20 g of polyester and 10 g of thinner. Keyword : pumice, sands, polyester, polymer concrete, impact test and bending strength test.